Interpretation of Law and Intent - Avramović, Dragutin; Jovanov, Ilija D (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Abstract: The authors start from the assumption that the intention of the legislator is an element that the interpreter should not neglect when understanding the text of the law. Intention can be understood in different ways, wider and narrower, as a psychic moment, but also as a manifested intention. The most prominent opponents of the concept of collective psychological intention come from the school of legal realism, criticizing the standpoints and manners of resolving many important cases in the practice of the highest courts in the United States of America. The authors conclude that it is absurd to understand legislative intent as a concept that aims to read the minds of members of the legislature. But also, the point of view that the legislator, just because it is a collective body, has no intention regarding the topic it discusses and passes the most important regulations in the state, takes the same degree of bizarreness. It must be assumed that the legislature always has a rational will that reflects the attitude of the people towards the policy that the parliamentary majority stand for in the elections. Consequently, it is sometimes possible to give an answer how would legislator solve a certain dilemma if it was set to him. The intention of the legislator might be very useful in interpretation, but it must be kept in mind that it does not solve every particular problem in interpretation and that it is sometimes just a guideline for the mindset of a disciplined judge who will always seek for the meaning that the legislature wanted to express with the words used.
Keywords: legislative intention; legal meaning of words; Max Radin; efficiency in judicial decision-making.